Investigation on the Horizontal Landing Velocity and Pitch Angle Impact on the Soft-Landing Dynamic Characteristics - Qing Lin; Jie Ren (International Journal of Aerospace Engineering)
The dynamic analysis of the soft landing of the lunar probe is very important to the design of the probe. The initial movement and attitude parameters of the probe during landing have a direct influence on the landing impact. In order to investigate the lunar probe soft-landing dynamic impact by different initial horizontal velocities, pitch angles, and inclinations of the lunar slope, an inertial force-based 7-DOF soft-landing dynamic model is applied under two conditions: the upward and downward slope landing surfaces. The impact on the dynamic characteristics of soft landing is analyzed in terms of body displacement, body overload, and the forces of the primary and secondary buffer struts due to the change of initial horizontal velocity and initial pitch angle of the probe. The result shows that, in 2-2 landing mode, the stress conditions on the primary and secondary struts are obviously impacted by initial horizontal velocity, and the initial pitch angle affects the body overload and the loading state of the secondary buffer strut. The body overload and landing impact could be significantly mitigated if the lunar probe’s horizontal landing speed is limited within 1 m/s, the pitch angle is limited within 12°, and the landing is along the uphill terrain with the inclination of the lunar slope less and equal to 9°. The analysis can directly determine the range of the horizontal speed and pitch attitude angle to ensure the safety of landing, and provide a reference for the reasonable control design of the lander’s horizontal speed and pitch attitude.